Learning Islamic Religious Education Based on Ta'dib Perspective of Islamic Education Psychology at Muhammadiyah Pakel Elementary School - Dahuri Dahuri; Wantini Wantini (Universitas Muhammadiyah Yogyakarta, 2023)
Islamic Religious Education (PAI) has an important role in shaping the character and morality of students, so it is important to use a ta'dib-based learning approach, namely an approach that integrates religious values with academic learning, which has been recognized as an effective approach. However, to achieve the optimization of ta'dib-based PAI learning, it is important to pay attention to the perspective of Islamic educational psychology. This study aims to identify and analyze efforts to optimize ta'dib-based PAI learning from the perspective of Islamic educational psychology at Muhammadiyah Pakel Elementary School. The research method used is field research with a qualitative approach. Data were obtained through class observations, interviews with PAI teachers, and analysis of documents related to the PAI learning program at Muhammadiyah Pakel Elementary School. The results showed that the optimization of ta'dib-based PAI learning at Muhammadiyah Pakel Elementary School involved several strategies. First, the use of learning methods that emphasize the formation of noble character and Islamic ethics in students' daily activities. Second, the use of learning media that is relevant to Islamic values increases students' interest in and understanding of PAI material. Third, fostering effective communication between teachers and students, as well as cultivating mutual respect in the learning process. Meanwhile, the perspective of Islamic educational psychology can make a positive contribution to the development of student character because this approach can influence students' attitudes, values, and behaviour in accordance with religious teachings so that the psychology of Islamic education provides an understanding of the cognitive, affective, and psychomotor aspects of students that need to be considered in the learning process.